2015
DOI: 10.3389/fpsyg.2015.00679
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor strategies for recognizing geometrical shapes: a comparative study with different sensory substitution devices

Abstract: The sensorimotor approach proposes that perception is constituted by the mastery of lawful sensorimotor regularities or sensorimotor contingencies (SMCs), which depend on specific bodily characteristics and on actions possibilities that the environment enables and constrains. Sensory substitution devices (SSDs) provide the user information about the world typically corresponding to one sensory modality through the stimulation of another modality. We investigate how perception emerges in novice adult participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 74 publications
0
24
0
1
Order By: Relevance
“…This lead to a training duration of seven weeks for which a former study [28] had shown significant perceptual and behavioral changes. Previous studies examining sensory substitution [2123] showed that some perceptual aspects of the substituted stimulus were learned in a very short time whereas a prolonged training with the device developed a more detailed perception. Ward and Meijer [22] investigated late blind subjects with an auditory to vision substitution device and even after several years of daily use still observed perceptual changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lead to a training duration of seven weeks for which a former study [28] had shown significant perceptual and behavioral changes. Previous studies examining sensory substitution [2123] showed that some perceptual aspects of the substituted stimulus were learned in a very short time whereas a prolonged training with the device developed a more detailed perception. Ward and Meijer [22] investigated late blind subjects with an auditory to vision substitution device and even after several years of daily use still observed perceptual changes.…”
Section: Discussionmentioning
confidence: 99%
“…Learning how to use a sensory substitution device needs time. While subjects learn some perceptual aspects of the substituted stimulus in a very short time, prolonged training with the device develops a more detailed perception [2123]. However, it has been argued that no true substitution is achieved, and that acquired skills are better described by the analogy to reading [24].…”
Section: Introductionmentioning
confidence: 99%
“…For practical purposes the comparison is appropriate, since it allows us to analyze in detail a complex sequence of sensorimotor patterns. Other studies have described the same analogy in sound localization tasks in humans 20 , in owls 38 , studying echolocation abilities in humans 54 and bats 55,56 , and with the use of sensory substitution devices in humans 57 . It would be interesting to study if there are common mechanisms in different sensory modalities that account for the emergence of saccade-like patterns.…”
Section: Discussionmentioning
confidence: 77%
“…In the same way that the physiology of the brain shapes vision, the engineering of each different SSD sets limitations on the type and quality of visual information available. The angle of the camera-sensor (field of view) for example or nature of the sensor information (distance information vs. contrast information or edges of objects) and the way this information is conveyed, influence how the SSD user explores the environment (Bermejo et al, 2015). Regardless of the type of visual information transferred, or the modality used by the device (tactile or auditory), the distal attribution process is a crucial step in developing strategies when using SSDs (Siegle and Warren, 2010).…”
Section: Spatial Perception Strategies and Sensory Substitution Devicesmentioning
confidence: 99%